Kliničke karakteristike i liječenje majmunskih boginja kod ljudi - Moisova, Diana L; Daguf, Vladislav A; Grebennikova, Maria A; Tretyakova, Yuliya A; Oflidi, Georgy K; Filonov, Anton R (Scripta Medica, 2023)
The COVID-19 pandemic is abating, but the threat of a new epidemic is growing due to the spread of monkeypox in non-endemic regions of the world. In 2022, there were the monkeypox outbreaks throughout Europe, in the Western Hemisphere. With the cessation of the vaccine, due to the global eradication of smallpox, outbreaks of monkeypox have become more common. Currently, there are no exact recommendations for complex treatment and alleviation of the monkeypox symptoms for infected people. Under these conditions, it is especially important to know the pathogenetic mechanisms and epidemiology of the virus for the most effective containment of its spread, especially in view of the negative experience gained in combating the COVID-19 epidemic. The purpose of this study was to summarise the known data on the epidemiology, clinical course and treatment of monkeypox, as well as an attempt to assess the possibility of a new world-spanning pandemic. A targeted search was performed on the keywords “monkeypox”, “virology”, “Tecovirimat”, “Cidofovir”, “Brincidofovir” in PubMed, in the period up to July 2022. 661 articles were reviewed, among them as reviews, original research and clinical trials. Preference was given to articles in English that dealt in most detail with cases of monkeypox infection outside the Africa and included comments on the therapy. Seventeen articles were selected and analysed, as well as links within them for additional information on the case. It was revealed that monkeypox is mainly treated with maintenance therapy and the treatment of more complex cases is based on the use of specific antiviral drugs: Tecovirimat, Cidofovir, Brincidofovir. However, there is no widespread therapeutic practice for these drugs. Little is currently known about the monkeypox virus; the transmission of infection, the animal reservoirs, the host range and the prospects for specific treatment are not fully understood. Sharing resources and data with outbreak tracking around the world will greatly facilitate the process of learning about the virus and how to deal with it effectively.